A common framework for using and reporting consumer purchase data (CPD) in foodborne outbreak investigations in Europe. Issue 1 (1st January 2022) - Jore, Solveig; Braae, Uffe Christian; Trier Møller, Frederik; Friesema, Ingrid; Paranthaman, Karthik; Jalava, Katri; Jourdan-DaSilva, Nathalie; Löf, Emma; Rehn, Moa; Ethelberg, Steen
ABSTRACT: Consumer purchase data (CPD) can be a powerful tool in the investigation of foodborne outbreaks through analyses of electronic records of food that individuals buy. The objective of this study was to develop a common framework for use of CPD in foodborne outbreak investigations using the expertise of European public health professionals from 11 European countries. We also aimed to describe barriers and limitations preventing CPD utilization. CPD are mainly gathered from supermarket loyalty programmes, smaller consortia, and independent supermarkets. Privacy legislation governing CPD was perceived as the most crucial barrier for CPD usage, but still resolvable. The main practical challenges were obtaining consumer consent for CPD usage, the associated workload, data access, format, and analysis. Harmonising methods and reporting across countries, standardised consent forms and electronic consent methods were identified as solutions. This guideline was developed to support outbreak investigators in overcoming barriers in using CPD, thereby increasing public health professionals' application and value of this powerful investigation tool. In addition, we hope this framework will lead to more public health institutions, in collaboration with food safety authorities, making use of CPD in outbreak investigations in the future.